Comparative Gross Anatomical Studies on the Seventh Cervical Vertebrae of Chiru (Pantholops hodgsoni) and Sheep (Ovis aries) - Choudhury, Abdur Rezzaque; Khan, Massarat; Quadir, Ajaz; Ahmad Baba, Mushtak; Ahmad John, Masuood; Ahmad Dar, Firdous; Sheikh, Andleeb Rafiq (International Journal of Livestock Research, 2018)
The present study was conducted on the seventh cervical vertebrae of chiru and sheep to arrive at their comparative gross anatomical differences. The morphometrical features of seventh cervical vertebra of chiru were studied, and compared with the same characteristics and parameters of the same vertebrae of sheep. The body was longest (4.3cm) and widest of all the cervical vertebrae of chiru and as compared to the vertebrae of sheep (3.2±0.06cm). Posterior concavity of the body of both chiru and sheep presented on either side a demi facet, a characteristic feature of this vertebra for articulation with 1st rib. Concavity of the posterior end of body was shallower than that of sheep. Morphmetric analysis of these vertebrae revealed that the values of different biometrical parameters were generally higher in chiru as compared to sheep which could act as a forensic tool to identify species.